2009
DOI: 10.1186/1471-2288-9-36
|View full text |Cite
|
Sign up to set email alerts
|

How well do adolescents recall use of mobile telephones? Results of a validation study

Abstract: BackgroundIn the last decade mobile telephone use has become more widespread among children. Concerns expressed about possible health risks have led to epidemiological studies investigating adverse health outcomes associated with mobile telephone use. Most epidemiological studies have relied on self reported questionnaire responses to determine individual exposure. We sought to validate the accuracy of self reported adolescent mobile telephone use.MethodsParticipants were recruited from year 7 secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 35 publications
3
49
1
Order By: Relevance
“…A further source of uncertainty is the emitted exposure from mobile phones, in particular during data traffic and in stand-by mode (Urbinello and Röösli 2013) and errors in modelling and personal measurements ). In our study, self-reported mobile phone call duration is highly overestimated as seen in other studies of adolescents, although not to that extent (Aydin et al 2011;Inyang et al 2009). For that reason we put a lot of effort to consider objectively recorded mobile phone call duration in our analysis for at least a subgroup of our cohort.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A further source of uncertainty is the emitted exposure from mobile phones, in particular during data traffic and in stand-by mode (Urbinello and Röösli 2013) and errors in modelling and personal measurements ). In our study, self-reported mobile phone call duration is highly overestimated as seen in other studies of adolescents, although not to that extent (Aydin et al 2011;Inyang et al 2009). For that reason we put a lot of effort to consider objectively recorded mobile phone call duration in our analysis for at least a subgroup of our cohort.…”
Section: Discussionmentioning
confidence: 50%
“…This study relied on self-reported mobile phone use only, which has been shown to be inaccurate. Adolescents tend to substantially overestimate their amount of mobile phone use (Aydin et al 2011;Inyang et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This residual variance is likely to reflect substantial error variance in the self-report measures concerning frequencies of talking and texting. Previous studies show that recall accuracy for mobile phone use is only moderate, in both adolescents (Inyang, Benke, Morrissey, McKenzie, & Abramson, 2009) and adults (Timotijevic et al, 2009Vrijheid et al, 2006Vrijheid et al, 2009), with substantial random error and typically about 20% underestimation of call number and 40% overestimation of call duration. Thus, the observed heritabilities and genetic correlations estimated from these self-report data are probably lower than the true values.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that adolescents tend to overestimate their mobile phone use (Aydin et al 2011;Inyang et al 2009). This especially holds for duration of mobile phone calls and less pronounced for frequency of calls.…”
Section: Strengths and Limitationsmentioning
confidence: 99%